Hubungan Antara Regulasi Emosi Dengan Tingkat Stres Kerja Pada Perawat Di Rumah Sakit Manado Medical Center - Sahari, Sahari; Paputungan, Dhea Kurniaty (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2023)
This study aims to determine the relationship between emotion regulation with the level of work stress of nurses. This study uses an approach quantitative with correlation analysis. The subjects were nurses at RSU Manado Medical Center with a total of 78 nurses. The sampling technique used wa the total sampling technique. Data collection methods using an emotional regulation scale is based on Thompson’s theory of 16 valid points (α = 0,834). The work stress scale is based on Robbins and Judge’s theory of 52 points valid (α = 0,933). The results of data analysis showed that there was a negative correlation significant relationship between emotional regulation and work stress levels with score of -0,608 and p = 0,000 < 0,05. This means that the higher the emotional regulation, the more low level of work stress. Furthermore, this research also shows that emotional regulation has an influence on work stress by 37%. Keyword: Nurse, Emotion Regulation, Work Stress